Design and synthesis of carborane-containing estrogen receptor-beta (ERβ)-selective ligands. Issue 19 (1st October 2015) - Ohta, Kiminori; Ogawa, Takumi; Oda, Akifumi; Kaise, Asako; Endo, Yasuyuki
Graphical abstract